A comparison of clinical practice guidelines for proximal femoral fracture. (5th November 2012) - Kearns, R. J.; Moss, L.; Kinsella, J.
Summary Clinical practice guidelines are designed to assist clinical decision‐making by summarising evidence and forming recommendations. The number of available guidelines is vast and they vary in relevance and quality. We reviewed guidelines relevant to the management of a patient with a fractured neck of femur and explored similarities and conflicts between recommendations. As guidelines are often produced in response to an area of clinical uncertainty, recommendations differ. This can result in a situation where the management of a particular clinical problem will depend upon which guideline is followed. We explore the reasons for such differences.